Perlindungan Hukum Terhadap Barang Konsumen (Bagasi Tercatat) Dalam Menggunakan Transportasi Udara (Studi Di Bandar Udara Internasional Minangkabau) - Dwikornida, MHD. Jeihan (Normative Jurnal Ilmiah Hukum, 2026)
Law Number 1 of 2009 concerning Aviation stipulates that carriers are responsible for losses suffered by passengers if checked baggage is lost, destroyed, or damaged while in the carrier's possession. This research was conducted at Minangkabau International Airport, managed by PT Angkasa Pura Indonesia. The research questions are: (1) What is the form of legal protection for checked baggage according to Law Number 1 of 2009 concerning Aviation? and (2) What are the obstacles faced by airlines in implementing legal protection for checked baggage users and what are the solutions to these problems. The type of research used is normative legal research combined with an empirical approach. Normative research is conducted through literature studies of laws and regulations, documents, and legal literature, while empirical research is conducted through interviews with informants and respondents in the field. The results of the study indicate that the form of legal protection for checked baggage includes the issuance of baggage tags during the check-in process, monitoring of baggage movement routes with CCTV, the provision of Lost and Found Counters, and the provision of compensation in the form of cash or one-shot compensation in accordance with applicable legal provisions. However, the implementation still faces a number of obstacles, including economic factors, limited quality of human resources, machine damage, negligence of ground handling officers, and negligence of passengers in guarding or reporting baggage. Solutions taken by airlines include imposing strict sanctions in the form of dismissal of officers who violate, additional supervision through CCTV cameras, and settlement of claims in accordance with the Standard Operating Procedures for Handling Baggage Processing and Settlement of Baggage Irregularities issued by Angkasa Aviasi Servis. Based on these findings, it can be concluded that legal protection is still not optimal due to various obstacles, so that it is necessary to improve human resources, update technology, and improve the claim settlement mechanism so that legal protection can be realized optimally.